Effect of Density and Viscosity on Injection Characteristic of Jatropha - waste Cooking Oil Biodiesel Mixture. - Mariono, Mariono; Wahyudi, Wahyudi; Nadjib, Muhammad (Universitas Muhammadiyah Yogyakarta, 2023)
Biodiesel has an important role in the world of transportation and its existence is taken into account. So the availability of biodiesel fuel in the future will be difficult to eliminate and must continue to be fulfilled. Therefore, it is necessary to innovate to increase the availability of biodiesel fuel. Biodiesel can be made from biological materials and includes renewable energy as a substitute for diesel oil. The production of biodiesel in this study jatropha and waste cooking oil as raw materials. This study aims to determine the effect of density and viscosity on the injection characteristics of jatropha-waste cooking oil biodiesel mixtures (1:4 and 4:1) on various B5-B40 fuels. Production of biodiesel from jatropha and waste cooking oil through degumming, esterification and transesterification processes. The results showed that the jatropha-waste cooking oil biodiesel mixed with 1:4 level B15 and 4:1 mixed with B10 level complied with SNI 7182-2015 biodiesel standards. The higher the density and viscosity values of jatropha-waste cooking oil biodiesel, the narrower the spray angle and the longer the spray penetration